(untitled) (Journal of NELTA, 2016)
This study is an examination of the effect of the different degrees of explicitness of written corrective feedback (WCF) on implicit and explicit knowledge of the target structure (past simple tense) in the short term and long term. There were four experimental groups including a control group, in this quasi-experimental study which received different degrees of explicit WCF. This study sought to investigate whether or not written corrective feedback could also be effective in targeting the problematic error category in the texts of FL writers. Past simple test was known as the problematic structure based on the result of the pre-test, though their level of proficiency was intermediate. It was found that both metalinguistic and direct WCF could affect the participants’ explicit knowledge of the past simple tense in the short term and long term; the indirect WCF on the other hand, could only affect the explicit knowledge in the short term and the reformulation was the only kind of WCF that did not have any effect on the explicit knowledge of the past simple tense. Moreover, all the experimental groups’ implicit knowledge improved in the short term; however, this improvement was sustained in the long term for the metalinguistic and indirect groups only. Journal of NELTA, Vol. 21, No. 1-2, 2016, Page:74-85